福建近海姥鲨肝油中角鲨烯的分离测定 - 王军; 翁幼竹; 苏永全; 郑微云; 余群 (2002)
采用薄层层析和气相层析法分离、检测了福建近海姥鲨 (Cetorhinusmaximus)幼鱼肝脏中角鲨烯含量 ,结果表明 :1)采用正已烷为展开剂的薄层层析法 ,碳氢化合物中角鲨烯的回收率可达 95 % ;2 )姥鲨肝脏中肝油和碳氢化合物含量存在明显的性别差异 ,但肝脏和肝油中角鲨烯含量无明显性别差异 ,分别为 0 .31% (♀ )、0 .32 % (♂ )和 0 .4 0 %(♀ )、0 .4 6 % (♂ ) ;3)福建近海姥鲨肝脏中角鲨烯含量明显高于福建近海其它鲨鳐类 Squalene from the livers of shark Cetorhinus maximus collected from Pingtan Island, Fujian Province was isolated and determined by thin layer chromatography and gas chromatography. The results showed: 1) the recovery rate of squalene isolated from hydrocarbon of the shark by thin layer chromatography with the eluent of n hexane was 95%; 2) there were obvious differences in contents of oil and hydrocarbon in livers between female and male shark, but contents of squalene in liver and oil of the shark liver seemed almost the same, with 0.31%(♀)?0.32%(♂) and 0.40%(♀)?0.46%(♂) respectively; 3) contents of sequalene of C. maximus were much richer than those of other sharks and rays collected from Fujian coastal.